(untitled) (Journal of Information Technologies in Education (ITE), 2014)
A brief analysis of the social and economic aspects of the development of DL systems in the Arab world has been offered. Three key elements in the provision of educational services has been considered. The problems of development and sustainable growth of distance learning systems have been discussed.